Falastin al hadara 'abr al tarikh : Palestinian civilization throughout history - AlTamimi, Joud Halawani; Darat Al Funun- The Khalid Shoman Foundation (Amman; Darat Al Funun, The Khalid Shoman Foundation, 2018)
Falastin al Hadara book, reflecting Darat al Funun$1 (Bs 2017 exhibition and events program showcasing Palestinian civilization and cultural heritage throughout the ages, bringing to life the untold story of Palestine. The year 2017 marks 100 years since the 1917 Balfour Declaration, 70 years since the 1947 UN resolution for the Partition of Palestine, and 50 years since the 1967 Arab-Israeli war. Within this context, Darat al Funun-The Khalid Shoman Foundation dedicated its 2017 exhibition and events program to showcasing the continuity of Palestinian history and cultural heritage throughout the ages under the title (3z(BFalastin al Hadara(3y(B, Palestine the civilization throughout history. Beginning with the ancient history of Palestine, a year-long program has been organised that includes in-depth talks on archaeology and architecture, early printed press and radio, Palestinian poets and writers, photography, and history of music and popular culture before 1948. Pioneering Palestinian artists from the early 20th century are exhibited side by side with contemporary artists. Storytelling, theatre, film screenings and music.s
English; Russian
Keywords: Cultural history exhibition; N4390-5098 Visual Arts. Exhibitions; Palestine